Essentials of services marketing - Wirtz, Jochen (Pearson Education South Asia Pte Ltd, 2012)
Includes bibliographical references and indexes.; Essentials of Services Marketing" masterfully integrates rigorous academic research, theory and cutting-edge management thinking. A superb read that covers all key aspects of marketing and managing services - ranging from consumer behavior to strategy, and from revenue management to service leadership. It's a great source to consult whether you are redesigning service processes, developing service recovery policies, implementing a loyalty program, or want to significantly improve the service quality delivered by your people.